2018
DOI: 10.1108/ijchm-03-2016-0160
|View full text |Cite
|
Sign up to set email alerts
|

To help or not to help: antecedents of hotel employees’ organizational citizenship behavior

Abstract: Purpose Drawing on organizational support theory, this study aims to propose and test a moderated path analysis to explore the interactive effect of perceived supervisor support and supervisors’ organizational embodiment on organizational citizenship behavior, as well as the mediating effect of perceived organizational support. Design/methodology/approach Hypotheses are tested using two-phase survey data collected from 398 dyads of employees and their immediate supervisors from 26 (three-to-five star) hotels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 65 publications
3
47
0
1
Order By: Relevance
“…To date, extant research has identified many determinants of OCB such as perception of organizational politics (Khan et al, 2019), emotional intelligence (Lim et al, 2018), perceived organizational support (Dai et al, 2018), psychological contract fulfillment (Ahmad and Zafar, 2018), and ethical leadership (Yang and Wei, 2017;Mostafa, 2018). However, little is known about whether humble leadership can affect OCB, and the potential mechanisms accounting for this relationship is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…To date, extant research has identified many determinants of OCB such as perception of organizational politics (Khan et al, 2019), emotional intelligence (Lim et al, 2018), perceived organizational support (Dai et al, 2018), psychological contract fulfillment (Ahmad and Zafar, 2018), and ethical leadership (Yang and Wei, 2017;Mostafa, 2018). However, little is known about whether humble leadership can affect OCB, and the potential mechanisms accounting for this relationship is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the purpose of the study is to measure the impact of retail system antecedents (Leadership support, Empowerment and Professional Development) on the organizational citizenship behavior through job satisfaction as a mediating variable. To express the study's problem the researchers relied on the recommendations of Alotaibi, A.G. (2001), (Halepota & Shah, 2011); Jha, (2014) Bilgin, et al, (2015); (Jain, 2016); Ahmad, & Zafar, (2018), (Dai et al, 2018); and (Rubel & Rahman, 2018) who underlined the value of citizenship behavior, and the positive yield organizations got to confront the threat of competitors, and to achieve better outcomes.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Within the same context Dai et al, ( 2018) stated that the behavior of support leaders has a remarkable influence on individuals and organization outcomes. Theoretically it has been proven that human resources represented the inimitable competitive advantage (Armstrong & Tayler 2014), so that it is crucial to equip them with continuous development and learning programs to boost their capabilities to be able to perform successfully current and future jobs (Moh'd, 2019).…”
Section: Leadership Supportmentioning
confidence: 99%
“…According to the theory of organizational support, perceived organizational support should emberikan reciprocity that leads to an obligation to help organizations (Kurtessis et al, 2016). Based on previous studies, organizational citizenship behavior is one factor that gives the advantage to the organization (Podsakoff et al, 2009;Somech & Zahavy, 2013;Knippenberg et al, 2015;Dai et al, 2016). That is because the organizational citizenship behavior can improve organizational performance (Turnipseed & Rassuli, 2005).…”
Section: Introductionmentioning
confidence: 99%